Associations of adherence to physical activity and dietary recommendations with weight recurrence 1-5 years after metabolic and bariatric surgery - Sundgot-Borgen, Christine; Bond, Dale S.; Rø, Øyvind; Sniehotta, Falko F.; Kristinsson, Jon; Kvalem, Ingela Lundin (Surgery for obesity and related diseases, 2024)
Background - Little is known about longer-term adherence to recommended physical activity (PA) and dietary behaviors after metabolic and bariatric surgery (MBS) and whether adherence is associated with weight recurrence. - Objectives - To explore (1) changes in and associations between adherence to PA and general dietary recommendations after MBS and (2) whether PA and dietary behaviors interact to predict weight recurrence. - Setting - University hospital; public practice. - Methods - Participants completed ActiGraph PA monitoring, dietary questionnaire, and weighing 1 and 5 years after surgery. Parametric and non-parametric tests evaluated changes in and associations between adherence to PA and dietary recommendations. Multiple linear regression explored associations of adherence and weight recurrence 5 years post-surgery. - Results - A total of 73 participants (66% loss to follow-up, 80.8% females) were included. From 1 to 5 years after surgery, adherence to PA recommendations did not change (23.5% versus 20.5%, P = .824), whereas adherence to dietary recommendations decreased (P = <.001). Adherence to PA recommendations is positively associated with eating fruits and vegetables and limiting intake of sugar and fat at 1 year (P < .05) and negatively associated with choosing meat with less fat at 5 years (P = .018). Adherence to PA and dietary behaviors did not independently contribute or interact to predict weight recurrence. - Conclusions - Adherence to recommendations was poor. Dietary adherence decreased from 1 to 5 years post-surgery, whereas PA adherence remained stable. PA adherence was positively associated with adherence to some dietary recommendations at 1 year but not at 5 years. Neither behavioral adherences were associated with weight recurrence. Additional research is needed to understand how to improve adherence and its relationship with other health outcomes after MBS.
Gesehen am 15.11.2024